PERBANDINGAN FUNGSI PARU ANTARA NELAYAN PENYELAM TAHAN-NAPAS DAN NELAYAN BUKAN PENYELAM DI KOTA AMBON TAHUN 2018 - Evan Christian Oetama; June Luhulima; Josepina Mainase (Fakultas Kedokteran Universitas Pattimura, 2019)
Breath-hold diving is a traditional method used by fishermen to catch fish or other sea creatures. When humans hold their breath during diving, their body will develop physiological changes generally, with regular exercise can improve lung function. Based on many studies that have reported, there’s an increase in lung function in breath-hold diving fishermen. The results of Maluku Health Profile in 2014 shows 39.90% of healthy living behavior. Unhealthy behavior affects individuals and society in health. The aim of this study is to determine the comparison of pulmonary function between breath-hold diving fishermen and non-divers fishermen with the same background of healthy behavior in Ambon City in 2018. This study uses analytical methods with cross-sectional approach using primary data of 15 breath-hold diver subyekts and 15 non-divers fishermen. Data were analyzed using SPSS and T Test indepedent. The characteristics such as age, weight, height, body mass index, blood pressure, and pulse were measured. The results of this study by measuring pulmonary function using parameters VC, FVC, and FEV1% with spirometry, obtained a mean value of lung function comparison between breath-hold diving fishermen and non-lung function fishermen in vital capacity (VC) ratio (p = 0.03) (3.48 ± 0.5 vs 3.01 ± 0.63), forced vital capacity (FVC) (p = 0.045) (2.19 ± 0.45 vs 1.84 ± 0.46), forced expiratory volume in one second (FEV1%) (p = 0.03) (91.46 ± 9.12 vs 83.44 ± 10.3). The lung function comparison in breath-hold diving fishermen and non-diver fishermen found that p value ≤ 0.05, so there’s a significant difference of lung function between breath-hold fishermen and non-diver fishermen. The conclusion of the research is, with the same background of life behavior, the lung function of breath-hold diving fishermen is better than non-diver fishermen. Suggestions for people can exercise breath-hold diving for underwater recreation or maintain health especially in the lung organs by studying breath-hold diving fishermen.